Pengaruh latihan box drill dan small sides games terhadap kemampuan passing pada pemain SSB HW Mandiangin - Ulfaizin, Muhammad Syifa; Rakhman, Arie; Mulhim, Muhammad (Jurnal Porkes, 2024)
The purpose of this study is to determine the effect of the training methods of box drill and small side games on the passing ability of SSB HW Mandiangin players between the ages of 13 and 15. The players have not been able to pass properly, so frequent passing errors become a problem in playing soccer. The type of research used is experimental research with the design of "Two Group Pretest-Posttest Design". The research location was conducted at SSB HW Mandiangin. The population of this study were all the players of SSB HW Mandiangin with a total of 35 people. The sample was selected as many as 18 people using purposive sampling technique. Grouping is done through ordinal pairing after pretest results. The data collection instrument uses a soccer passing ability test. Data analysis uses normality test, homogeneity test, hypothesis test or t-test and independent t-test. The t-test of the box drill training group has a significant value of 0.001  0.05, while the small sides games group has a significant value of 0.002  0.05. So the conclusion of the two groups is that there is a significant influence on the passing ability of SSB HW Mandiangin players. The box drill training method has a better effect than the small sides games training method based on the average post-test value.